Bowel Preparation for Elective Colorectal Procedures: A Review of Clinical Effectiveness, Cost-Effectiveness, and Guidelines - Sara D. Khangura; Philip la Fleur; Charlene Argáez; Lorna Adcock (My University, 2018)
• Objective: Compare clinical effectiveness and cost‑effectiveness of parenteral antibiotic prophylaxis with or without oral antibiotics and/or mechanical bowel preparation (MBP) in preoperative care for elective colorectal procedures. Also review existing evidence-based guidelines. • Findings: Limited data from randomized controlled trials (RCTs) suggest adding MBP to intravenous antibiotics may reduce surgical site infections (SSI), whereas adding oral antibiotics alone shows no benefit. Confidence in results is low due to methodological limitations. No cost-effectiveness studies were identified. • Guidelines: Among seven guidelines reviewed, four recommend combined MBP and oral antibiotics; others either recommend oral antibiotics alone or advise against MBP without oral antibiotics. Evidence basis remains limited
Keywords: mechanical bowel preparation (MBP); oral antibiotic prophylaxis; intravenous antibiotic prophylaxis; elective colorectal surgery; surgical site infection; clinical effectiveness; cost-effectiveness; evidence-based guidelines